The Experience of the Madrasah Principal in Overcoming Teachers' Resistance to Educational Quality Innovation at MTs. Unggulan Fathussalam Muncar - Ma’sum, Abdulloh Hannan (SAINTIS Publishing, 2025)
This study aims to analyze the experience of the madrasah principal in overcoming teachers' resistance to educational quality innovation at MTs. Unggulan Fathussalam Muncar through an empathy-based leadership approach and open communication. The research employs a qualitative approach with a case study design, allowing for an in-depth exploration of the dynamics of change within this pesantren-based educational institution. Data collection techniques include in-depth interviews with the madrasah principal, teachers, and staff, participatory observations, and documentation related to the implementation of innovation and communication strategies. The collected data is analyzed using thematic analysis techniques to identify key themes, including the role of empathetic leadership, open communication, and non-material incentives in reducing resistance and increasing teachers' participation. The findings reveal that the principal’s humanistic approach, characterized by transparent communication and teacher involvement in the change process, successfully fosters a collaborative work environment. Non-material rewards also prove effective in strengthening teachers' intrinsic motivation and accelerating their acceptance of educational innovation. This study makes a significant contribution to understanding empathy-based leadership and the implementation of educational innovation in pesantren settings.